Phthalide Derivatives from Angelica Sinensis Decrease Hemoglobin Oxygen Affinity: A New Allosteric-Modulating Mechanism and Potential Use as 2,3-BPG Functional Substitutes - Wei-Ren Chen (Nature Portfolio, 2017)
Abstract Angelica sinensis (AS), one of the most versatile herbal medicines remains widely used due to its multi-faceted pharmacologic activities. Besides its traditional use as the blood-nourishing tonic, its anti-hypertensive, anti-cardiovascular, neuroprotective and anti-cancer effects have been reported. Albeit the significant therapeutic effects, how AS exerts such diverse efficacies from the molecular level remains elusive. Here we investigate the influences of AS and four representative phthalide derivatives from AS on the structure and function of hemoglobin (Hb). From the spectroscopy and oxygen equilibrium experiments, we show that AS and the chosen phthalides inhibited the oxygenated Hb from transforming into the high-affinity “relaxed” (R) state, decreasing Hb’s oxygen affinity. It reveals that phthalides cooperate with the endogenous Hb modulator, 2,3-bisphosphoglycerate (2,3-BPG) to synergetically regulate Hb allostery. From the docking modeling, phthalides appear to interact with Hb mainly through its α1/α2 interface, likely strengthening four (out of six) Hb “tense” (T) state stabilizing salt-bridges. A new allosteric-modulating mechanism is proposed to rationalize the capacity of phthalides to facilitate Hb oxygen transport, which may be inherently correlated with the therapeutic activities of AS. The potential of phthalides to serve as 2,3-BPG substitutes/supplements and their implications in the systemic biology and preventive medicine are discussed.